Pengaruh Pemberian Edukasi Mengenai Ultra-Processed Food (UPF) Terhadap Peningkatan Pengetahuan, Perubahan Sikap, dan Perilaku pada Siswa/i SMAN 37 Jakarta - Tri Ardianti Khasanah; Rifany Fitri Aulia; Alya Patriawati; An’Nur Septi Susanti; Elsi Nurhayati; Prisca Putrihana (PPNI UNIMMAN, 2025)
One type of food that is widely consumed by adolescents is packaged food. In Indonesia, the prevalence of adolescents aged 16-18 years with overnutrition status reached 13.5%. One striking phenomenon is the increasing consumption of ultra-processed foods (UPF), which are commonly found in the daily diet of adolescents. These products include items such as chips, candy, biscuits, bread, cereals, nuggets, sausages, instant noodles, sweetened drinks, and many more. The consumption of these foods has raised concerns due to their potential health risks, including the risk of overnutrition, obesity, and other related diseases. As adolescents are at a critical stage of growth and development, it is essential to address the issue of UPF consumption and its impact on their health. Efforts to combat this issue require educational interventions that inform adolescents about the dangers and long-term effects of consuming UPF. This includes counseling on the importance of selecting healthier food options. The aim of this extension program is to evaluate the effectiveness of education on UPF consumption through counseling sessions at SMAN 37 Jakarta. The educational program used an interactive technology-based learning approach combined with visual media, offering a digital learning experience that engages students effectively. Based on the results of the extension activities conducted at SMAN 37 Jakarta, it can be concluded that the educational intervention successfully improved students' knowledge, attitudes, and behaviors regarding healthy food consumption. The results from the pre-test and post-test revealed a significant increase in students' understanding of the harmful effects of UPF consumption and the importance of making healthier food choices.